Nietzsche e a teologia liberal : de David Strauss à teologia da morte de Deus - Faria, Jonas Silva (2017)
Nietzsche's relation to liberal theology comes from the moment in which the philosopher reads The Life of Jesus, of David Strauss. When the German philosopher refers directly or indirectly to Christian theology, he goes through a path once opened by liberal theologians, and more specifically by Strauss, who in his writings had already harshly criticized the Christian tradition. In the course of this work, we examine how much theology was important for Nietzsche and also how his criticisms to the Christian theology later influenced and paved the way for the so-called theology of the death of God in the twentieth century, more specifically in the United States. For this reason, this dissertation seeks to show that liberal theology was important for Nietzsche, mainly because the philosopher mentioned above wrote the First Extemporaneous to criticize the theologian David Strauss and later the work The Antichrist, in which he utters harsh criticisms to the Theology of the nineteenth century and, in general, to the Christian tradition.